2022
DOI: 10.3390/nu14030503
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol Suppresses Inflammatory Biomarkers Production by Lipoteichoic Acid- and Peptidoglycan-Stimulated Human Tonsil Epithelial Cells

Abstract: Pharyngitis is an inflammation of the pharynx caused by viral, bacterial, or non-infectious factors. In the present study, the anti-inflammatory efficacy of carvacrol was assessed using an in vitro model of streptococcal pharyngitis using human tonsil epithelial cells (HTonEpiCs) induced with Streptococcus pyogenes cell wall antigens. HTonEpiCs were stimulated by a mixture of lipoteichoic acid (LTA) and peptidoglycan (PGN) for 4 h followed by exposure to carvacrol for 20 h. Following exposure, interleukin (IL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…In addition, Glutathione and Glutathione Peroxidase were elevated with carvacrol, providing protection against the ROS species generated from high glucose levels. Similar anti-inflammatory findings were seen with human tonsil epithelial cells stimulated with Lipoteichoic Acid and Peptidoglycan [ 36 ]. IL-6, IL-8, ENA-78, and GCP-2 were all suppressed with carvacrol.…”
Section: Carvacrolsupporting
confidence: 77%
“…In addition, Glutathione and Glutathione Peroxidase were elevated with carvacrol, providing protection against the ROS species generated from high glucose levels. Similar anti-inflammatory findings were seen with human tonsil epithelial cells stimulated with Lipoteichoic Acid and Peptidoglycan [ 36 ]. IL-6, IL-8, ENA-78, and GCP-2 were all suppressed with carvacrol.…”
Section: Carvacrolsupporting
confidence: 77%
“…Another study reported that both carvacrol and p-cymene inhibit the activity of the same enzyme; however, p-cymene had a stronger effect when compared to carvacrol [86]. The antiinflammatory potential of carvacrol is reported in different models of inflammation, such as IL-1β-stimulated chondrocytes [116], rheumatoid arthritis [117], carcinogenicity associated inflammation in rat colon [118], tonsil epithelial cells [119], paw edema animal model [120], LPS-activated HL-1 cardiomyocytes [121], ovalbumin-induced asthma animal model [122], encephalomyelitis [123] and MNNG-induced gastric carcinogenesis [124]. Rosmarinic acid, the major component in the HRW, is also widely known for its anti-inflammatory properties alone [125][126][127][128][129][130][131][132][133] and in nanovesicles [134] or associated with chitosan [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBD-2 production was significantly suppressed during the 24 h carvacrol treatment. Carvacrol also had an effect on PGE2 and COX-2 levels in cell suspensions [91].…”
Section: Antioxidant and Anti-inflammatory Activity Of Carvacrolmentioning
confidence: 90%